ESTUDO DA INCORPORAÇÃO DE VIDRO DE PARA-BRISA EM MASSA DE PORCELANA SILICOSA E ALUMINOSA - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2012)
The glass is not a biodegradable material, which causes an environmental problem when it is discarded. However, it is a material that can be 100% recycled, or even re-used, but the laminated glass (glass windshields) is not accepted for recycling, this because it is a glass of low particle size and also by the difficulty of separating the glass polymer film, while this type of glass consisting of two or more layers of glass held together by one or more layers of a polymer called polyvinyl butyral (PVB). Thus it is necessary to find alternative means which allow recycling. In this thesis was studied the possibility of incorporating laminated glass in the ceramic bodies of siliceous and aluminous porcelain, replacing feldspar which acts as a flux these two ceramic bodies. The objective of this research is to verify the changes that the incorporation of glass windshields because the glassy phase of siliceous and aluminous porcelain and reflections that these changes have on the ceramic properties. Was chosen for this particle sizes of two glass laminate, and a thin, rough and added to another ceramic body in amounts of 5%, 10% and 15%, by weight replacing the same amount of feldspar. The powders of these mixtures were pressed and sintered at three different temperatures. Sintered porcelains were characterized through measurements of porosity, bulk density, water absorption, modulus of rupture by three point bending, X-ray diffraction, scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS). The compositions siliceous and aluminous porcelain were introduced laminated glass of finer showed very similar results to those of composition without addition of laminated glass.
Keywords: vidro laminado; porcelana; sinterizadas; laminated glass; porcelain; sintered; CNPQ::ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA